An extension and a refinement of van der Corput's inequality - Jian Cao; Da-Wei Niu; Feng Qi (International Journal of Mathematics and Mathematical Sciences)
van der Corput's inequality is extended and refined by using Euler-Maclaurin formula and other analytic techniques.